2012
DOI: 10.1016/j.bpj.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

STED Microscopy with Optimized Labeling Density Reveals 9-Fold Arrangement of a Centriole Protein

Abstract: Super-resolution fluorescence microscopy can achieve resolution beyond the optical diffraction limit, partially closing the gap between conventional optical imaging and electron microscopy for elucidation of subcellular architecture. The centriole, a key component of the cellular control and division machinery, is 250 nm in diameter, a spatial scale where super-resolution methods such as stimulated emission depletion (STED) microscopy can provide previously unobtainable detail. We use STED with a resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 51 publications
9
88
0
Order By: Relevance
“…Cep164, as a marker of the mother basal body in primary cilia, was reported to localise to all basal bodies in MCCs (Lau et al, 2012). Our findings show a colocalisation of ELMO1 with Cep164 in both cell types ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Cep164, as a marker of the mother basal body in primary cilia, was reported to localise to all basal bodies in MCCs (Lau et al, 2012). Our findings show a colocalisation of ELMO1 with Cep164 in both cell types ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Superresolution techniques overcome the limits imposed on conventional microscopy by diffraction of light and resolve what was previously seen by conventional immunostaining as an unstructured blob into a tiny cylinder (Sillibourne et al 2011;Fu and Glover 2012;Lau et al 2012;Lawo et al 2012;Mennella et al 2012;Sonnen et al 2012). In this way, the mature Drosophila centrosome, for example, has been resolved into five major regions and three for its engaged daughter (see Fig.…”
Section: Structure and Duplication Cycles Of Centriolar Centrosomesmentioning
confidence: 99%
“…Immunoelectron microscopy demonstrated the localisation of CEP164 to the distal end of the mother centriole . Dual photoactivated localization microscopy (PALM) and stochastic optical reconstruction microscopy (STORM) imaging has localised CEP164 in a ring around the centriole barrel with a periodic enrichment of the signal within the ring (Sillibourne et al, 2011), and stimulated emission depletion microscopy has found that the enriched CEP164 signal corresponds to nine symmetricallyarranged clusters around the centriole, indicative of its association with each of the nine distal appendages (Lau et al, 2012).…”
Section: Introductionmentioning
confidence: 99%